PENGARUH KOMPENSASI FINANSIAL DAN KOMPENSASI NON FINANSIAL TERHADAP KINERJA KARYAWAN PADA PT KALIMARAU JAYA DI TANJUNG REDEB: PENGARUH KOMPENSASI FINANSIAL DAN KOMPENSASI NON FINANSIAL TERHADAP KINERJA KARYAWAN PADA PT KALIMARAU JAYA DI TANJUNG REDEB - Andi Fras Setyo (ECO-BUILD, 2019)
The purpose of this thesis is to determine the effect of financial compensation and non-financial compensation on employee performance at PT Kalimarau Jaya in Tanjung Redeb. The analytical tool used in this study is multiple linear regression. From the results of employee performance analysis using multiple linear regression, it can be interpreted as follows: The constant value is 7,258. This means that in a state of financial compensation and non-financial compensation the value is fixed or in a state of no influence from Financial Compensation and Non-Financial Compensation, the level of employee performance will move up or down by 7,258. The financial compensation regression coefficient is negative with a coefficient of -0.011. This shows that the financial compensation variable has a negative effect and not in the direction of employee performance. If the level of financial compensation falls by 1 percent, the performance level of PT Kalimarau Jaya's employees in Tanjung Redeb will decrease by 0,011 and vice versa. Non-financial compensation regression coefficient is positive with a coefficient of 0.563. This shows that the non-financial compensation variable has a positive and direct effect on employee performance. If the level of non-financial compensation rises by 1 percent, the performance level of PT Kalimarau Jaya's employees in Tanjung Redeb will also increase by 0.563 percent and vice versa.